Globalization and cultural heritage: rebuilding local identities - Rotman, Monica (2003)
New articulations are outlined actually instead of globalization process. In this setting, the concept "national" adopts a new preeminence and it is expressed through specific cultural ways. Paradoxically, in a globalizated context, countries suffer an outdoors process of homogeneization and an inner fragmentation one. In this context, a revitalization process of "national identity" arises strongly. These happens in our research, in periodical events organized by the national state. This cultural phenomena are based on the recovery and rebuilding of "national identity" Our case study is the "Traditional Handicrafts and Popular Traditions Fair" in Mataderos neighborhood in Buenos Aires city.